Early Cretaceous nannofossils and planktonic foraminifera from northern Gargano (Apulia, Italy) - COBIANCHI M.; LUCIANI, Valeria; BOSELLINI, Alfonso (Cretaceous Research, 1997)
The study of two Lower Cretaceous stratigraphic sections from northern Gargano, Apulia, southern Italy, has shown that the classic succession of the Umbria-Marche Basin, central Italy, can be extended to the south as far as the Gargano Promontory. Here, the Cretaceous basinal succession consists of three formations: the Maiolica, the Scisti a Fucoidi and the Scaglia. Near the margin of the platform, the Mattinata Formation with frequent gravity-displaced deposits, laterally substitutes the Maiolica Formation. According to our integrated biostratigraphic data, and in agreement with the classic chronostratigraphic schemes proposed from the Umbria-Marche Basin, the Scisti a Fucoidi of northern Gargano correlates with the late part of the early Aptian (C. litterarius Zone p. p., L. cabri Zone) to the late Albian (lower part of the P. achlyostaurion Zone and B. breggiensis Zone, T. praeticinensis Subzone). The occurrence of two anoxic episodes, which can be correlated with the 'Urbino level' and 'Amadeus segment' of the Umbria-Marche Basin, also strongly supports the proposed correlation of the two basins.